The Originality of China’s Aid Policy to Africa - Bayala, Viviane; Badiane, Kemo (Recent Trends in Arts and Social Studies Vol. 3, 2023)
This study highlights the singularity of China’s aid in Africa as it is rooted on the country’s strategic culture. Using document analysis and oral sources, this study reexamines the Chinese approach in the field of development assistance. It is based on the premise that the Chinese aid policy in Africa combines realism and idealism to achieve its foreign policy goals in Africa, and this singularity is deeply rooted in old-fashioned principles deriving from the Chinese strategic culture. China’s foreign aid policy aims at improving its international image, about which it cares very deeply, and which contradicts the conventional wisdom argument that China supports violators of human rights. China’s aid policies in general are less specific about the cultural singularity of China’s bilateral aid policy in African countries. Aid is at the same time realistic and flexible. It is realistic because it obeys to conditions which match China’s political and economic interests. To show this assertion is relevant, the article includes three sections. The first section explores the cultural principles which determine the Chinese foreign policy as a whole, whereas the last two sections analyze their (principles) relevance on the realist and idealist dimensions of the Chinese aid policy in Africa.